Relación entre los estilos de crianza parentales y el desempeño conductual en niños con discapacidad - Castro Petitjean, Diego (2021)
Parental styles are a key component when we discuss about raising children and they have a major influence in many development variables. The objective in this study was to review the evidence of parenting styles and its relation with behavioral performance in children with disability. To this end, we conducted a review report of contemporary literature of the constructs (parenting styles, behavior and disability), taking into consideration only the ones that met the requirements of PRISMA (Urrútia & Bonfill, 2010). The following data bases were used: Scopus, Ebsco, ProQuest, Psycinfo and PubMed. The selected studies (n = 7) conducted correlational or comparative analysis between parenting styles and behavioral performance. As results go, we observed an indirect relation between functional parenting practices (authoritative style, acceptance, autonomy, limit setting) and behavioral problems; while the relation was found to be indirect with disfunctional parenting styles (authoritarian, permissive, reject, control).